CFD study of some factors affecting performance of HAWT with swept blades. Issue 5 (28th May 2017) - Khalafallah, M.G.; Ahmed, A.M.; Emam, M.K.
Abstract : Most modern high-power wind turbines are horizontal axis type with straight twisted blades. Upgrading power and performance of these turbines is considered a challenge. A recent trend towards improving the horizontal axis wind turbine (HAWT) performance is to use swept blades or sweep twist adaptive blades. In the present work, the effect of blade curvature, sweep starting point and sweep direction on the wind turbine performance was investigated. The CFD simulation method was validated against available experimental data of a 0.9 m diameter HAWT. The wind turbine power and thrust coefficients at different tip speed ratios were calculated. Flow field, pressure distribution and local tangential and streamwise forces were also analysed. The results show that the downstream swept blade has the highest C p value at design point as compared with the straight blade profile. However, the improvement in power coefficient is accompanied by a thrust increase. Results also show that the best performance is obtained when the starting blade sweeps at 25% of blade radius for different directions of sweep.